On the Succession of Sarmatian Cultures and Population (Based on the Materials of the Kalinovsky Burial Mound) - Mariya A. Balabanova (Нижневолжский археологический вестник, 2018)
The paper presents the results of a new research into the archaeological and anthropological materials of the Kalinovka burial mound of the Sarmatian time. For the first time, these materials were investigated by V.P. Shilov and V.V. Ginzburg in 1959. On the basis of modern developments in archaeology of Sarmatian antiquities and achievements of Russian and foreign anthropology, we present a fairly objective picture of the interaction of local and foreign components of this site. Conservation of some elements of the funeral ceremony in the Early and Middle Sarmatian times, the foundation of burial cemeteries without disturbing the graves of predecessors, as well as the similarity of morphological type of these chronological groups allows concluding that the members of one paleopopulation, possibly including a small number of “foreigners”, were buried in the studied burial mound. The research results based on different methods, including the method of multidimensional statistics, show that the materials of the Late Sarmatian time are completely different from those of the Early and Middle Sarmatian times.